INVESTIGATION ON LONG DISTANCE TRANSPORTATION OF FISH I. TRANSPORTATION OF FROZEN FISH FROM COCHIN TO CULCUTTA - GOVINDAN, T K; GUPTA, SIBSANKAR; CHATTOPADHYAY, P. CHATTOPADHYAY (Fishery Technology, 2017)
Oil Sardine ( Sardinella longfceps), mackerel ( Rastrelliger kanagurta), cat fish (Arius sp.), threadfin bream (Nemipterus japonicus) and ribbon fish (Trichurus sp.) were frozen in glazed/ unglazed blocks, packed in expanded polystyrene (EPS) insulated plywood boxes with and without additional ice and despatched in uninsulated parcel vans of trains from Cochin to Calcutta. The consignments reached the destination in excellent condition and were readily disposed off.